2015
DOI: 10.1007/s10900-015-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Free Fecal Immunochemical Test Disbursement in Eight Family Physician Offices

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death. CRC screening with a fecal immunochemical test (FIT) is important as occult blood may be detected. To offer Iowa Research Network members in family physician offices the opportunity to provide FITs at no charge to patients in need and determine how many of the tests would be handed out to patients and how many would be returned to the office. Eight family physician offices agreed to participate and 50 two-day FITs were provided, potentially p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(27 reference statements)
1
0
1
Order By: Relevance
“…The rate of noncompletion of the test could have been more if reminder calls were not made and the sample collected in the patient's home, in some cases. The noncompletion rate in this study is lower than that reported by Daly et al 31 in Iowa, in which only 51% of participants returned the kits, and by Steele et al in Scotland 32 , who reported a nonreturn rate of 39.4% despite the provision of prepaid mailing of kits; no reminder calls were made. The use of reminder systems for both the patient and doctor has been reported by Baker et al 33 to increase the rate of completion of the FIT.…”
Section: Discussioncontrasting
confidence: 73%
“…The rate of noncompletion of the test could have been more if reminder calls were not made and the sample collected in the patient's home, in some cases. The noncompletion rate in this study is lower than that reported by Daly et al 31 in Iowa, in which only 51% of participants returned the kits, and by Steele et al in Scotland 32 , who reported a nonreturn rate of 39.4% despite the provision of prepaid mailing of kits; no reminder calls were made. The use of reminder systems for both the patient and doctor has been reported by Baker et al 33 to increase the rate of completion of the FIT.…”
Section: Discussioncontrasting
confidence: 73%
“…There was another study with participants from a similar age range of 40-70 years, where the mean age was 57 years, which was not that different from our findings. 8 There was no significant age difference between the male and female participants of our study, which was similar to the findings of another study. 5 Some other studies with younger study participants reported that the incidence rate among adults younger than age 50 years is increasing due to an increase in left-sided tumors.…”
Section: Discussionsupporting
confidence: 91%